Computer Graphics Tracing cybernetic flows. - Turk, Stephen (Performance Research, 2006)
The article discusses the development of the historical trajectory of digital visualization system between contemporary methods and models of spatial mapping manifested in the use of computers in the U.S. In 1950s and early 1960s computer graphics was developed to solve problems concerning the representation of certain complex phenomena particularly in dealing with dynamics. The article identifies modes of thinking and strategies for performance as a fluid set of conditions.